Effect of DC Voltage on Prototype of Biodiesel Electrostatic Separator with Glycerin from Waste Cooking Oil - Jaya Utama Putra; Leila Kalsum; Yohandri Bow (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2018)
The limitations of fossil fuel support on fulfillment of energy need in a sustainable and environment friendly fashion has drove society to efforts of finding and developing fresh and renewably resources. Biodiesel is one the renewable energy resource and shows environment friendly property, consist of alkyl of fatty acids monoester originated from vegetable oil or animal fat.One of important steps in biodiesel production is separation of glycerin from product. Electrostatic method has been proved in accelerating saturation of glycerin. However, several aspects still need a careful assessment to acquire biodiesel production process with standard quality assigned. In this work, we designed an electrostatic separator of biodiesel from glycerin using waste cooking oil feed. The prototype was tested in several different voltages 12 Vdc, 20 Vdc, 30 Vdc and 33.5 Vdc. The result shows the highest voltage obtained is 33.5 Vdc, separation time 2 minutes 10 seconds having viscosity, water content and density i.e. 7.2139 cSt, 0.0321% and 0.85 g/mL respectively whereas flash point increase to 1917 C. The data confirmed that the product fulfills required standard value fordensity, water content and flash point.